CRYPTOSPORIDIUM-MALNUTRITION INTERACTIONS: MUCOSAL DISRUPTION, CYTOKINES, AND TLR SIGNALING IN A WEANED MURINE MODEL - Costa, Lourrany B. (2011)
Cryptosporidiosis is a leading cause of persistent diarrhea in children in impoverished and developing countries and has both a short- and long-term impact on the growth and development of affected children. An animal model of cryptosporidial infection that mirrors closely the complex interaction between nutritional status and infection in children, particularly in vulnerable settings such as post-weaning and malnourishment, is needed to permit exploration of the pathogenic mechanisms involved. Weaned C57BL/6 mice received a protein-deficient (2%) diet for 3–12 days, then were infected with 5 × 10(7) excysted C. parvum oocyts, and followed for rate of growth, parasite stool shedding, and intestinal invasion/morphometry. Mice had about 20% reduction in weight gain over 12 days of malnutrition and an additional 20% weight loss after C. parvum challenge. Further, a significantly higher fecal C. parvum shedding was detected in malnourished infected mice compared to the nourished infected mice. Also, higher oocyst counts were found in ileum and colon tissue samples from malnourished infected mice, as well as a significant reduction in the villous height–crypt depth ratio in the ileum. Tissue Th1 cytokine concentrations in the ileum were significantly diminished by malnutrition and infection. mRNA for toll-like receptors 2 and 4 were diminished in malnourished infected mice. Treatment with nitazoxanide did not prevent weight loss or parasite stool shedding. These findings indicate that, in the weaned animal, malnutrition intensifies cryptosporidial infection, while cryptosporidial infection further impairs normal growth. Depressed TLR2 and 4 signaling and Th1 cytokine response may be important in the mechanisms underlying the vicious cycle of malnutrition and enteric infection.